Bcl11b is essential for group 2 innate lymphoid cell development - FALLON, PADRAIC (My University, 2015)
Group 2 innate lymphoid cells (ILC2s) are often found associated with mucosal surfaces where they contribute to protective immunity, inappropriate allergic responses, and tissue repair. Although we know they develop from a common lymphoid progenitor in the bone marrow (BM), the specific lineage path and transcriptional regulators that are involved are only starting to emerge. After ILC2 gene expression analysis we investigated the role of Bcl11b, a factor previously linked to T cell commitment, in ILC2 development. Using combined Bcl11b-tom and Id2-gfp reporter mice, we show that Bcl11b is expressed in ILC2 precursors in the BM and maintained in mature ILC2s. In vivo deletion of Bcl11b, by conditional tamoxifen-induced depletion or by Bcl11b(-/-) fetal liver chimera reconstitution, demonstrates that ILC2s are wholly dependent on Bcl11b for their development. Notably, in the absence of Bcl11b there is a concomitant expansion of the RORγt(+) ILC3 population, suggesting that Bcl11b may negatively regulate this lineage. Using Nippostrongylus brasiliensis infection, we reveal that the absence of Bcl11b leads to impaired worm expulsion, caused by a deficit in ILC2s, whereas Citrobacter rodentium infection is cleared efficiently. These data clearly establish Bcl11b as a new factor in the differentiation of ILC2s.
PUBLISHED
Keywords: Genetics; Immunology, Inflammation & Infection